Extracellular Vesicles in Rheumatoid Arthritis and Systemic Lupus Erythematosus: Functions and Applications - Zhang, Bo; Zhao, Ming; Lu, Qianjin (Frontiers in Immunology, 2021)
In the last two decades, extracellular vesicles (EVs) have aroused wide interest among researchers in basic and clinical research. EVs, small membrane vesicles are released by almost all kinds of cells into the extracellular environment. According to many recent studies, EVs participate in immunomodulation and play an important role in the pathogenesis of autoimmune diseases. In addition, EVs have great potential in the diagnosis and therapy of autoimmune diseases. Here, we reviewed the latest research advances on the functions and mechanisms of EVs and their roles in the pathogenesis, diagnosis and treatment of rheumatoid arthritis and systemic lupus erythematosus.